Characterization of a second sterol‐esterifying enzyme in Toxoplasma highlights the importance of cholesterol storage pathways for the parasite. Issue 5 (3rd February 2013) - Lige, Bao; Sampels, Vera; Coppens, Isabelle
Summary Lipid bodies are eukaryotic structures for temporary storage of neutral lipids such as acylglycerols and steryl esters. Fatty acyl‐CoA and cholesterol are two substrates for cholesteryl ester (CE) synthesis via the ACAT reaction. The intracellular parasite Toxoplasma gondii is incapable of sterol synthesis and unremittingly scavenges cholesterol from mammalian host cells. We previously demonstrated that the parasite expresses a cholesteryl ester‐synthesizing enzyme, TgACAT1. In this article, we identified and characterized a second ACAT‐like enzyme, TgACAT2, which shares 56% identity with TgACAT1. Both enzymes are endoplasmic reticulum‐associated and contribute to CE formation for storage in lipid bodies. While TgACAT1 preferentially utilizes palmitoyl‐CoA, TgACAT2 has broader fatty acid specificity and produces more CE. Genetic ablation of each individual ACAT results in parasite growth impairment whereas dual ablation of ACAT1 and ACAT2 is not tolerated by Toxoplasma. ΔACAT1 and ΔACAT2 parasites have reduced CE levels, fewer lipid bodies, and accumulate free cholesterol, which causes injurious membrane effects. Mutant parasites are particularly vulnerable to ACAT inhibitors. This study underlines the important physiological role of ACAT enzymes to store cholesterol in a sterol‐auxotrophic organism such as Toxoplasma, and furthermore opens up possibilities of exploiting TgACAT as targets for the development of antitoxoplasmosis drugs.